Additive manufacturing of superparamagnetic micro-devices for magnetic actuation (Transactions on Additive Manufacturing Meets Medicine, 2019)
3D microstructures with sub-micron resolution can be manufactured in additive manner applying multi-photon laser structuring technique. This paper is focused on the incorporation of superparamagnetic iron oxide nanoparticles into the photoresist in order to manufacture micrometer-sized devices featuring a magnetic moment. The aim of the project is to achieve untethered actuation of the presented objects through externally applied magnetic fields. Future medical application scenarios such as drug delivery and tissue engineering are targeted by this research.